International consensus on sports, exercise, and physical activity participation during post-operative interventions for Adolescent Idiopathic Scoliosis: An e-Delphi study - Susanna Tucker; Nicola R. Heneghan; Alison Rushton; Adrian Gardner; Emily Russell; Andrew Soundy (PLoS ONE, 2026)
Introduction Physiotherapists and surgeons have a significant role in promoting participation and offering a graded return to sports, exercise, and physical activity following spinal fusion in adolescent idiopathic scoliosis (AIS). However, there is a lack of evidence to guide post-operative rehabilitation and variability worldwide. This study aims to obtain consensus on 1) when it is safe and 2) how an individual with AIS might return to sports, exercise, and physical activity. Methods and analysis An international electronic 3 round Delphi study was conducted and reported. Eligible expert surgeons or physiotherapists had either specific clinical or research experience in AIS. Round 1 included a series of open-ended questions, from which a series of statements were generated. Round 2 commenced with a summary of the existing literature for participants to review prior to rating statements on a 5-point Likert scale. Participants were also given the opportunity to make comments. Round 3 participants were asked to re-rate statements on the same 5-point Likert scale. Consensus was determined through content analysis of open comments >1 participant, for statements rated on the 5-point Likert >75% agreement (strongly agree or agree) were defined as having consensus, following round 3 Kendall’s coefficient of concordance was calculated to evaluate the strength of the agreement where >75% was achieved. Results From 53 recruited participants (18 countries, 1 unknown), 41 responded to round 1, 32 to round 2, and 29 to Round 3 (14 surgeons, 15 physiotherapists). Round 1 generated 85 statements under 19 themes surrounding graded return to sports, rehabilitation milestones, philosophical approaches, and treatment modalities. Round 2 generated 56 statements, > 75% with seven split into two due to multiple concepts, yielding 63 statements across 9 themes with >75% agreement. Themes included overarching considerations of care, the MDT, physiotherapy treatment modalities, pre-operative care, inpatient stay, and post-operative rehabilitation phases 1, 2, 3, and 4. Round 2 open comments generated a further 22 statements. Round 3 generated 66 statements with >75% agreement across the same 9 themes. All round 3 statements demonstrated significance (p < 0.001) with moderate agreement (W = 0.5). A Wilcoxon Sum-rank result (p < 0.05) showed stability between rounds 2 and 3. An additional 5 recommendations were generated from round 3 open comments exploring types of post-operative exercise, provision of rehabilitation, timeframes and milestones, and MDT involvement. Conclusion This Delphi study provides the first international consensus of 71 statements on return to sports, exercise, and physical activity following spinal fusion in AIS. However, further subgroup analysis demonstrated consensus among surgeons and divergence among physiotherapists highlighting the need for further exploration of these statements.